Implementation Of Character Education Through Student Morning Culture Program At Al-Ulum Terpadu Islamic High School Medan - Fadilah, Mutiara Adha; Maulana Nst, Zahra Magfirah; Hasibuan, Zahra Ummu Aiman; Abdurrasyid, Abdurrasyid; Juniarsih, Frizkiya (Universitas Syiah Kuala, 2025)
This study aims to determine how the implementation of the morning cultum program supports character education for students at SMA Islam AL-Ulum Terpadu Medan. Especially there are still some students who are still lacking in discipline when the morning cultum program is implemented at school. The research method used is qualitative. Data collection procedures with observation, interviews, documentation. The obstacles found in this study are the lack of student discipline in following the morning cultum at school and the habit of student discipline at school with discipline at home is still not effective. The solution provided by the school to students is to provide motivation as a support for students who still need guidance